1994
DOI: 10.1007/bf00714591
|View full text |Cite
|
Sign up to set email alerts
|

Temperature acceleration in cold oral stimulation

Abstract: This study measured the temperature acceleration of a cold probe as it contacts human tissue. Both the effects of touching a cold probe to the oral cavity were investigated. The results indicated a rapid warming pattern. This warming is effected first by temperature changes resulting from the probe being moved from ice into room temperature and second by the contact to oral mucosa. In fact, in some cases, the probe had reached minimal cold sensation levels by the time it reached the oral cavity. Results also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
9
1
1
Order By: Relevance
“…The chilling effect imposed by a laryngeal mirror might have been too small to be detected in this study. The temperature of a small probe moved from ice to the oral mucosa has been shown to increase significantly within a few seconds (10). However, in the present study there is no reason to believe that the mirror temperature, and hence the results, differed systematically.…”
Section: Discussioncontrasting
confidence: 63%
“…The chilling effect imposed by a laryngeal mirror might have been too small to be detected in this study. The temperature of a small probe moved from ice to the oral mucosa has been shown to increase significantly within a few seconds (10). However, in the present study there is no reason to believe that the mirror temperature, and hence the results, differed systematically.…”
Section: Discussioncontrasting
confidence: 63%
“…4). Probably because of clinical limitations, previous studies investigating thermal stimulation and swallowing focused mainly on the influences and physiologic mechanism of cold, rather than warm, stimuli on elicitation, rather than performance, of swallowing [13,15,28]. Videofluorographic analysis of liquid temperature on oropharyngeal swallowing indicated that 1 ml of cold liquid causes longer (compared to control) pharyngeal response times and longer (compared to control) laryngeal elevation in normal subjects [11].…”
Section: Discussionmentioning
confidence: 94%
“…Logemann's original protocol of``chilling a laryngeal mirror in ice'' [11, p.136] prior to stimulation is useful for ease of clinical application. However, Selinger et al [26] have shown that a metal probe encased in an insulator made of ceramic is perceptibly neutral within six seconds after removing it from the ice. The rapid increase in temperature of common metal probes would virtually prohibit their use in any controlled study of the eects of cold application on swallowing.…”
mentioning
confidence: 99%